Effects of PDLA molecular weight on the crystallization behaviors and rheological properties of asymmetric PDLA/PLLA blends. (27th March 2023) - Yan, Cong; Hou, De-Fa; Zhang, Kai; Yang, Ming-Bo
Abstract: The molecular weight of poly(d -lactide) (PDLA) and poly(l -lactide) (PLLA) affects the performance of their blends by controlling the formation and characteristics of stereocomplex (SC) crystals. In this work, the crystallization behaviors and rheological properties of asymmetric PDLA/PLLA (5/95, w/w) blends were carefully investigated considering the molecular weight of PDLA (Mn(PDLA) = 1.5 × 10 3 –18.7 × 10 3 g/mol) when the molecular weight of PLLA was selected as 5.0 × 10 4 g/mol. The results revealed that PDLA holding too low or too high Mn(PDLA) was unfavorable to the formation of SC crystallites owing to their weak interaction or difficult diffusion in the PLLA matrix, and the optimal Mn(PDLA) was ca. 5.4 × 10 3 g/mol. Given this optimal Mn(PDLA), the composite viscosity and tensile viscosity of the obtained PDLA/PLLA blend were increased by 2–3 orders of magnitude and 10 times compared with neat PLLA, respectively, due to the formation of SC crystals with a high content (ΔHm -SC of 26.0 J/g). Besides, this PDLA/PLLA blend showed a fast crystallization rate and strong solid-like viscoelastic behavior. This work revealed the regular correspondence between Mn(PDLA) and the performance of asymmetric PDLA/PLLA blends. Graphical abstract: Image 1 Highlights: The effect of Mn(PDLA) on the crystallization and rheology of asymmetric PDLA/PLLA blends was investigated. The relationship of Mn(PDLA) - SC crystallites - performance of PLA materials was revealed. The optimal Mn(PDLA) was ca. 5.4 × 10 3 g/mol when using PDLA to modify the PLLA matrix (Mn = 5.0 × 10 4 g/mol).